2015
DOI: 10.1242/jeb.118240
|View full text |Cite
|
Sign up to set email alerts
|

Vibrissal sensitivity in a harbor seal (Phoca vitulina)

Abstract: Prior efforts to characterize the capabilities of the vibrissal system in seals have yielded conflicting results. Here, we measured the sensitivity of the vibrissal system of a harbor seal (Phoca vitulina) to directly coupled sinusoidal stimuli delivered by a vibrating plate. A trained seal was tested in a psychophysical paradigm to determine the smallest velocity that was detectable at nine frequencies ranging from 10 to 1000 Hz. The stimulus plate was driven by a vibration shaker and the velocity of the plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…If the vibration of the whisker shaft and deviations to the typical vibrational signal are detectable by the seal, they would provide salient information on the presence and nature of hydrodynamic stimuli. Recent psychophysical research on the vibrissal sensitivity of this species identified best sensitivity between 20 and 250 Hz and detectable signals up to 1000 Hz 10 . The signals recorded from the vibrissae in this study fall within the detectable range of the harbor seal, with much of the energy within the seal’s region of best sensitivity.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…If the vibration of the whisker shaft and deviations to the typical vibrational signal are detectable by the seal, they would provide salient information on the presence and nature of hydrodynamic stimuli. Recent psychophysical research on the vibrissal sensitivity of this species identified best sensitivity between 20 and 250 Hz and detectable signals up to 1000 Hz 10 . The signals recorded from the vibrissae in this study fall within the detectable range of the harbor seal, with much of the energy within the seal’s region of best sensitivity.…”
Section: Introductionmentioning
confidence: 98%
“…We recently reported that harbor seals are sensitive to mechanical vibrations from 10 Hz to 1,000 Hz 10 – a range that extends much higher than the frequency content of hydrodynamic signals produced by swimming organisms. Here we show that seal whiskers vibrate within the sensitive range of the animal, and that these vibrations are altered by encounters with hydrodynamic disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, seals are shown to distinguish between disturbances left by objects of different sizes and shapes [ 4 ], demonstrating that they can use their whiskers to discriminate among specific flow signatures, and likely among various prey types. To complement the hydrodynamic tracking experiments, systematic exploration of the whisker system’s tactile sensitivity in a live seal reveals the ability to detect perturbations on the order of 1 mm/s [ 5 ]. In controlled laboratory flume experiments, excised seal whiskers exhibit a broad range of frequency response in water flow with amplitudes noticeably influenced by the angle of attack, or orientation of the whisker, with respect to the freestream flow [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pinniped whiskers, in particular, have been studied, due to their prominence, high sensitivity (Hyvärinen and Katajisto 1984;Hyvärinen 1989;Dehnhardt et al 1998;Mauck et al 2000;Marshall et al 2006;Hyvärinen et al 2009;Erdsack et al 2014;McGovern et al 2014) and their ability to be moved using a network of voluntary muscles (Berta et al 2005). Indeed, Pinniped whiskers are capable of the tactile discrimination of object textures, shapes and sizes to a similar sensitivity as human fingertips (Dykes 1975;Murphy et al 2015) and can also detect fine-scale water movements, termed hydrodynamic sensing (Dehnhardt et al 2001;Wieskotten et al 2010a, b;Krüger et al 2018).…”
Section: Introductionmentioning
confidence: 99%